Movements Outside The Prayer Movements Done During Prayer From The Perspective Of The Hadith - Dwi Nurfana Acha Acha Dianti Ikrom; Muhammad Taufik (International Journal of Research, 2024)
This study focuses on the hadith of the Prophet Muhammad SAW which discusses movements outside the prayer movements that are done during prayer. Hadith has synonyms/mufrodif according to experts in the science of hadith, including sunnah, khabar, and atsar. Prayer in language is a prayer, while in terms of terminology it is a reading and certain actions that begin with takbir and end with greetings. Prayer is said to be invalid if one of its requirements and pillars is not carried out. There are several things that invalidate prayer, including performing movements outside the prayer movements, but on the other hand there are many hadiths of the Prophet SAW which explain that Rasulullah once performed movements outside the prayer movements, based on this a question arises regarding how to understand these hadiths, and how to implement these hadiths at this time. The purpose of the study was to determine the understanding of the hadith and to determine how to implement it at this time. This study is included in library research, using the maudhu'I method. The results of this study are, in terms of text, the hadiths may have the permissibility of performing movements outside of the prayer movements. However, if understood contextually, there are several things in the hadith that cannot be done because the situation and conditions in the past and present are different, and when we are going to perform the prayer movements there are limitations such as not being allowed to perform the movements three times in a row or performing excessive movements.